2000
DOI: 10.1590/s1517-83822000000200011
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Salmonella infection by contact using intestinal flora of adult birds and/or a mixture of organic acids

Abstract: This study was carried out to assess the ability of competitive exclusion and a mixture of organic acids to prevent Salmonella infection by contact between newly hatched chicks. A bird infected with Salmonella was placed in a box containing non-infected birds, previously treated with a broth culture of faeces of adult birds (CE) and/or a mixture of organic acids. The number of Salmonella organisms in the caeca of the contact birds was estimated at 4 and 8 days post-challenge. The birds were infected with Salmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 31 publications
4
16
0
Order By: Relevance
“…Several authors have suggested that multiple strains may be more useful than a single strain because they may act at different sites, in various modes, and probably in a synergistic manner [7,27,28]. It has also been hypothesized that mixtures of obligate and facultative anaerobic gut bacteria are more effective because the facultative anaerobes reduce oxygen levels in the anaerobic regions of the GIT, permitting the establishment of strictly anaerobic bacteria [29][30][31][32][33].…”
Section: Probiotics: Product Development and Purported Benefitsmentioning
confidence: 99%
“…Several authors have suggested that multiple strains may be more useful than a single strain because they may act at different sites, in various modes, and probably in a synergistic manner [7,27,28]. It has also been hypothesized that mixtures of obligate and facultative anaerobic gut bacteria are more effective because the facultative anaerobes reduce oxygen levels in the anaerobic regions of the GIT, permitting the establishment of strictly anaerobic bacteria [29][30][31][32][33].…”
Section: Probiotics: Product Development and Purported Benefitsmentioning
confidence: 99%
“…When water intake was reduced during the preslaughter feed withdrawal period, the consequent reduction in acid intake resulted in an increase in the number of viable SE in the crop (Avila et al, 2003). Oliveira et al, (2000) showed that organic acids added to the feed were not able to prevent infection of birds with S. Enteritidis, S. Agona, S. Infantis and S. Typhimurium serovars, but Berchieri Jr. and Barrow (1996) observed a remarkable reduction in mortality caused by Salmonella gallinarum, affecting the rate of infection between infected and uninfected birds. The results of the use of organic acids and/ or essential oils for Salmonella control may depend upon the Salmonella serovar used as a challenge organism (Oliveira et al, 2000;Santurio et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Oliveira et al, (2000) showed that organic acids added to the feed were not able to prevent infection of birds with S. Enteritidis, S. Agona, S. Infantis and S. Typhimurium serovars, but Berchieri Jr. and Barrow (1996) observed a remarkable reduction in mortality caused by Salmonella gallinarum, affecting the rate of infection between infected and uninfected birds. The results of the use of organic acids and/ or essential oils for Salmonella control may depend upon the Salmonella serovar used as a challenge organism (Oliveira et al, 2000;Santurio et al, 2007). Bacteriological examination of cloacal swabs and litter samples could be negative while the animals can carry Salmonella in their tissues and excrete it intermittently under certain stress conditions (Duchet-Suchaux et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Rantala (1974), to be fully effective, the protective material must be cultured under anaerobic conditions. However, recent studies have shown that aerobically incubated cecal cultures gave protection equal to that obtained from anaerobic incubation against S. typhimurium, S. infantis, S. agona, and S. enteritidis in newly hatched chicks (de Oliveira et al, 2000;Filho et al, 2003). Actually, this is not entirely surprising because static broth cultures develop very low redox potentials, due to the many facultative anaerobes in the inoculum, and thus obligate anaerobes may be able to multiply sufficiently.…”
Section: Mechanism Of Competitive Exclusionmentioning
confidence: 99%